2018
DOI: 10.1016/j.jphs.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of microRNA-93 inhibits TGF-β1-induced EMT and renal fibrogenesis by down-regulation of Orai1

Abstract: TGF-β1-induced excessive deposition of ECM and EMT process of tubular epithelial cells play critical roles in the development and progression of fibrosis in diabetic nephropathy (DN). Orai1 has been demonstrated to be involved in TGF-β1-induced EMT via TGF-β/Smad3 pathway. We are aimed to explore the effects of miR-93 on TGF-β1-induced EMT process in HK2 cells. In this study, our data showed that miR-93 was dramatically decreased in renal tissues of patients with DN and TGF-β1-stimulated HK2 cells. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Comparative miR expression profile arrays showed that miR-93 is a signature miR in hyperglycemic condition [24]. Up-regulation of miR-93 inhibits epithelial-mesenchymal transformation and renal fibrogenesis in TGF-β1-induced HK2 cells [25]. Although the biological functions of PTV1 and miR-93 in DN have been mentioned by previous studies, the detailed molecular mechanism of PTV1 involving miR-93 in DN remains unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Comparative miR expression profile arrays showed that miR-93 is a signature miR in hyperglycemic condition [24]. Up-regulation of miR-93 inhibits epithelial-mesenchymal transformation and renal fibrogenesis in TGF-β1-induced HK2 cells [25]. Although the biological functions of PTV1 and miR-93 in DN have been mentioned by previous studies, the detailed molecular mechanism of PTV1 involving miR-93 in DN remains unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, making miR-93 as the potential therapeutic option to alleviate DN. Importantly, miR-93 also negatively regulates the Calcium release-activated calcium channel protein-1 (ORAI1), and reduction of miR-93 expression in DN caused an increase in ORAI1 expression and subsequently promoted TGFB-mediated ECM accumulation and fibrosis (Ma et al, 2018). Excessive ECM accumulation will eventually lead to glomerulosclerosis; therefore, it is the first and crucial step for progressive renal function loss.…”
Section: Micrornas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 99%
“…In the present study, in order to simulate renal fibrosis in vitro , the human tubular epithelial cell line HK-2 was treated with TGF-β according to previous reports (19,20). The role of miR-21 in mediating the renal protective effect of quercetin was assessed using TGF-β-induced fibrosis in HK-2 cells to provide a theoretical basis for the treatment of nephropathy using quercetin.…”
Section: Introductionmentioning
confidence: 99%